The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/pan.13626
|View full text |Cite
|
Sign up to set email alerts
|

Regional anesthesia for sternotomy and bypass—Beyond the epidural

Abstract: Summary Systemic opioids have been the main stay for the management of perioperative pain in children undergoing cardiac surgery with sternotomy. The location, distribution, and duration of pain in these children have not been studied as extensively as in adults. Currently, there is no consensus to the dose of opioids required to provide optimum analgesia and attenuate the stress response while minimizing their unwanted side effects. At present there is a tendency to use lower dose aiming for early extubation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 68 publications
1
30
0
1
Order By: Relevance
“…It has been reported that superficial blockade of these nerves close to the surgical site could effectively control the pain associated with sternotomy, and thus risks of a central approach could be avoided. 15 The blockade of these nerves was performed by Chaudhary et al for the first time by the parasternal block technique in pediatric cardiac surgery practice. 16 These authors performed local anesthetic infiltration bilaterally to each intercostal space for the blockade of the Th2 to Th6 intercostal nerves before closure of the sternum; it was reported that postoperative opioid consumption was less, pain scores were lower, and time to extubation was shorter in pediatric patients who underwent parasternal block.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that superficial blockade of these nerves close to the surgical site could effectively control the pain associated with sternotomy, and thus risks of a central approach could be avoided. 15 The blockade of these nerves was performed by Chaudhary et al for the first time by the parasternal block technique in pediatric cardiac surgery practice. 16 These authors performed local anesthetic infiltration bilaterally to each intercostal space for the blockade of the Th2 to Th6 intercostal nerves before closure of the sternum; it was reported that postoperative opioid consumption was less, pain scores were lower, and time to extubation was shorter in pediatric patients who underwent parasternal block.…”
Section: Discussionmentioning
confidence: 99%
“…It also may reduce stress response activation and in adults, reduce the incidence of chronic pain, which for thoracotomies is 20% to 60% but much lower in children (1.9%-16%) and even lower in sternotomies. [6][7][8][9] Historically, regional techniques for cardiac surgery included spinal, epidural, and caudal anesthesia. Their use was limited because of possible serious complications such as an epidural hematoma associated with anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…13 Inadequate postoperative pain control is a substantial problem after surgery and results in reduced mobilization, increased morbidity, extended hospital stay, 14 development of chronic pain, 15 and loss of motivation for additional treatment, especially in pediatric patients. Therefore, there is a need for effective postoperative analgesic strategies, such as peripheral nerve blocks other than neuraxial anesthesia, for cardiac surgery with sternotomy, 1,4 with the minimization of opioidrelated side effects. [4][5][6] Advantages, Achievements, and Safety of TTP Block as a…”
Section: Discussionmentioning
confidence: 99%
“…The intercostal muscle layer consists of the following 3 layers: the external intercostal muscle, the internal intercostal muscle, and the innermost intercostal muscle. 1 The target layer for the TTP block, located between the intercostal muscle layer and the transverse thoracic muscle, is identified via ultrasound as a white line (Fig 1, B and C).…”
Section: Presurgical Scan Proceduresmentioning
confidence: 99%
See 1 more Smart Citation